Incidence of sight‐threatening diabetic retinopathy in people with Type 2 diabetes mellitus and numbers needed to screen: a systematic review. Issue 10 (12th March 2019) - Groeneveld, Y.; Tavenier, D.; Blom, J.W.; Polak, B.C.P.
Abstract: Aim: To investigate the incidence of sight‐threatening diabetic retinopathy in Type 2 diabetes mellitus. Background: In most countries, yearly or biennial screening intervals for diabetic retinopathy in people with Type 2 diabetes are recommended. Fewer screening sessions reduce the effort required of people with Type 2 diabetes and reduce healthcare costs. Methods: We conducted a search of PubMed, Embase, Web of Science and the COCHRANE Library for studies published betweeen 1 January 2000 and 1 January 2017. Eligible studies were those that included general populations of >100 people with Type 2 diabetes mellitus. Additional study population criteria were absence of moderate diabetic retinopathy or more severe diabetic retinopathy at last screening session and at least two gradable retinal screening sessions. Outcomes of interest in the included studies were moderate and severe non‐proliferative diabetic retinopathy (R2), proliferative diabetic retinopathy (R3) or maculopathy (M1), collectively known as sight‐threatening or referable diabetic retinopathy. Results: A total of 17 studies were included. In people with Type 2 diabetes without or with only mild diabetic retinopathy at baseline, the average incidence rates of sight‐threatening diabetic retinopathy were 1 per 100 person‐years and 8 per 100 person‐years, respectively. The average numbers needed to screen to detect one case of sight‐threatening diabetic retinopathy were 175 and 19 in people without and with mild retinopathy at last screening, respectively. Conclusion: In people with Type 2 diabetes without retinopathy at last screening, the incidence of severe sight‐threatening retinopathy at the subsequent screening session was low. In people with mild retinopathy, progression to sight‐threatening diabetic retinopathy was nearly 10‐fold higher. This review supports lengthening of the screening interval of patients with Type 2 diabetes without retinopathy at last screening session. What's new?: The incidence of sight‐threatening diabetic retinopathy (STDR) in people with Type 2 diabetes is decreasing, probably as a result of improving diabetes care. In screen‐detected mild retinopathy (R1), regression to no visible retinopathy (R0) is common. In people with mild retinopathy at baseline, development and detection of STDR by the time of the next screening visit is nearly 10 times more frequent than in people without retinopathy at baseline. Recent data on incidence and numbers needed to screen can be helpful in constructing optimal intervals for the screening of the large population of people with Type 2 diabetes with no or only mild retinopathy.